Penyusunan Materi Ajar Al Nahw Al Whazhifi dan Penerapannya Dalam Pembelajaran Bahasa Arab Untuk Mahasiswa PAI IAI Muhammadiyah Sinjai - Husnaini Jamil; Nur Agung; Takdir Takdir (IAIN Madura, 2020)
Learning Arabic in Indonesia has been going on for several decades, especially since the presence of Islam in Indonesian society. However, difficulties in understanding it still overshadow the majority of students and educators from various backgrounds, ranging from elementary, secondary, to tertiary levels. Many solutions are offered to overcome these difficulties, one of which is by changing the orientation of Arabic learning which initially leads to mastery of grammar to increase the ability of learners in the use of grammar as a means of communicating with Arabic that is good and accurate. This orientation change is realized by the preparation of various functional grammatical books that are applicable and can be adapted to the abilities, situations, and conditions of the learner. This study uses a type of R&D research with the Borg and Gall development model. The use of functional grammar material in this study provides an opportunity for learners to master Arabic more quickly and easily as evidenced by the value of -t table <-t count is -18,084 <-2,045.